2021
DOI: 10.1016/j.lanepe.2021.100212
|View full text |Cite
|
Sign up to set email alerts
|

Long working hours and risk of 50 health conditions and mortality outcomes: a multicohort study in four European countries

Abstract: SUMMARY Background Studies on the association between long working hours and health have captured only a narrow range of outcomes (mainly cardiometabolic diseases and depression) and no outcome-wide studies on this topic are available. To achieve wider scope of potential harm, we examined long working hours as a risk factor for a wide range of disease and mortality endpoints. Methods The data of this multicohort study were from two population cohorts from F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 58 publications
2
29
0
2
Order By: Relevance
“…[6][7][8] Many studies conducted recently have shown that working for long hours has a negative impact on physical and mental health. [9][10][11] Additionally, the workers' quality of life including physicians is undesirably affected by long working hours. As long working hours cause sleep disturbances and affect the efficiency of an individual's social role.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Many studies conducted recently have shown that working for long hours has a negative impact on physical and mental health. [9][10][11] Additionally, the workers' quality of life including physicians is undesirably affected by long working hours. As long working hours cause sleep disturbances and affect the efficiency of an individual's social role.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we examined lifestyle and mental health -related factors that predicted each trajectory. For self-rated health and working <35 hours/week, three distinctive clusters emerged: ( 1 ) “Slightly declining good health, and slightly increasing working time”; ( 2 ) “Sustained good health, and moderate but slightly increasing working time”; and ( 3 ) “Fairly good but declining health, short and decreasing working hours”.…”
Section: Discussionmentioning
confidence: 99%
“…We used group-based multi-trajectory analysis ( 18 ) to identify trajectories of health and working hours separately for ( 1 ) self-rated health and working <35 h/week; and ( 2 ) self-rated health and night work. Self-rated health was treated as continuous variable and working hour patterns were dichotomous variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the data we discussed in this paper on NCDs and risk factors relies on the GBD 2019, so we were not able to address those that were not included in the GBD. For example, in Chapter 5, rest is one of the priority areas for lifestyle improvement, and the target items are sleep and working hours: insufficient sleep and excessive working hours are known to be associated with health risks such as hypertension, other cardiovascular diseases, and diabetes 56 , 57 but are not covered in the current GBD.…”
Section: More Public Health Efforts Are Needed To Address Critical Ri...mentioning
confidence: 99%